Burnout and Moral Distress Among Social Workers Working with Children and Families Versus Those Who Do Not - Brend, Denise Michelle; Herttalampi, Mari; Mänttäri-van der Kuip, Maija (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2023)
Objectives: Burnout is of international concern among social workers, and recently moral distress (MD) has been identified among this professional group. Little is known about how burnout and MD experiences differ between social workers serving children and families (CF) and social workers in other domains. Less is known about the potential relationship between burnout and MD across these subgroups of social workers.Methods: This brief report examines if the levels of, and associations, between MD and burnout differ between a sample of Finnish CF social workers (n = 199) compared social workers in other domains (n = 168).Results: Based on multivariate analyses of covariance and hierarchical regression analyses, we found that working with children and families did not moderate the associations between MD and burnout. However, working with children and families was associated with higher levels of exhaustion, MD frequency, and distress. MD frequency and MD distress were also both significant predictors of burnout among the sample of social workers. CF social workers had higher levels of exhaustion compared to the other social workers.Implications: MD may be an important factor influencing the wellbeing of CF social workers. Organizations employing CF social workers are encouraged to investigate potential sources of MD and set workplace policies to reduce risks. More research examining causes of, and identifying effective remedies to, MD is warranted.